Efficiency and productivity differential effects of land certification program in Ethiopia: Quasi-experimental evidence from Tigray - Ghebru, Hosaena H.; Holden, Stein (International Food Policy Research Institute, 2013)
Taking advantage of a unique quasi-experimental survey design, this study analyzes the productivity impacts of the Ethiopian land certification program by identifying how the investment effects (technological gains) would measure up against the benefits from any improvements in input use intensity (technical efficiency). For this purpose, we adopted a data envelopment analysis–based Malmquist-type productivity index to decompose productivity differences into (1) within-group farm efficiency differences, reflecting the technical efficiency effect, and (2) differences in the group production frontier, reflecting the long-term investment (technological) effects.